Estructura de la población y crecimiento de Pinctada mazatlanica (Pterioida: Pteriidae), Golfo de Nicoya, Costa Rica - Solano López, Yonohide; Cabrera Peña, Jorge; cruz, Rafael A.; Palacios, J. A. (Revista de Biología Tropical, 1997)
Population size structure and growth were studied in Pinctada mazatlanica between September 1993 to September 1994, in Isla Pan de Azúcar, Golfo de Nicoya, Costa Rica. The population of specie are established mainly in those sites where there the substrate offers protected shelters. Population density was estimated a 2.42± 0.8 individuals per mª, related to the total explores area (220mª, between 0.4 m to 7.5 m depth). The most relevant morphometric variables for characterizing this species are shell height and shell width. The maximum height and weight found were 141.50 mm y 496.30 g respectively. The maximum class frequencies is 60-95 mm for the height (75% of the population). The equation of von Bertalanffy was A= 139.5 [1 - e ·O .083(t ·O .32)·O .55 xO .083/2.(Sin Zn(,·0.65).Sin.(O .32 · 0.65)for height and 445.46 [1 _ e·0.08l(, • 0.32)]3 for weight. Approximately 73.6% of the population is reached within twelve months, in the next twelve months increments are end the order of 3.88mm/mo, decreasing to 1.68 mm/mo in the last months. The relationship between shell height-weight was P= 5.31 X 10.5 A3.228, indicate isometric growth.